2021
DOI: 10.1007/s40121-021-00400-2
|View full text |Cite
|
Sign up to set email alerts
|

Computational and Experimental Studies Reveal That Thymoquinone Blocks the Entry of Coronaviruses Into In Vitro Cells

Abstract: Introduction Since December 2019, severe acute respiratory syndrome-related coronavirus-2 (SARS-CoV-2) has caused the coronavirus disease 2019 (COVID-19) pandemic in China and worldwide. New drugs for the treatment of COVID-19 are in urgent need. Considering the long development time for new drugs, the identification of promising inhibitors from FDA-approved drugs is an imperative and valuable strategy. Recent studies have shown that the S1 and S2 subunits of the spike protein of SARS-CoV-2 utiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 27 publications
0
27
0
5
Order By: Relevance
“…Using predictive modeling, we recently recommended TQ for both the prophylaxis and treatment of Covid-19 [9,10]. Several theoretical calculations [11][12][13] and clinical trials [14][15][16] have confirmed the predictive capability of our model. The integral protective properties and relevant physicochemical functions executed by TQ in both the extra-and intracellular space have been recently compiled [17]: In short, TQ is a small hydrophobic molecule with the capacity to bind to the viral spikes, to bind to the viral envelope, to oxidize the virus, to scavenge reactive oxygen species (ROS) -after oxidation of the virus -and to enter cells and raise endosomal pH.…”
Section: Methodsmentioning
confidence: 60%
“…Using predictive modeling, we recently recommended TQ for both the prophylaxis and treatment of Covid-19 [9,10]. Several theoretical calculations [11][12][13] and clinical trials [14][15][16] have confirmed the predictive capability of our model. The integral protective properties and relevant physicochemical functions executed by TQ in both the extra-and intracellular space have been recently compiled [17]: In short, TQ is a small hydrophobic molecule with the capacity to bind to the viral spikes, to bind to the viral envelope, to oxidize the virus, to scavenge reactive oxygen species (ROS) -after oxidation of the virus -and to enter cells and raise endosomal pH.…”
Section: Methodsmentioning
confidence: 60%
“…119 Interestingly, one in vitro study demonstrated that TQ showed significant antiviral activity against a SARSCoV-2 strain isolated from Egyptian patients, 120 possibly through blocking the entry of the virus into the cells. 121 Overall, the existing studies highlight the immense potential of TQ as an effective antiviral agent against COVID-19, a premise which is highly supported by the molecular docking studies examining TQ's effects against various virus and host cell targets, which are discussed in more detail in the following section.…”
Section: Antiviral Activitymentioning
confidence: 94%
“…120,[125][126][127] TQ has also demonstrated a good affinity against ACE2 receptors, which allows it to interfere with virus uptake into the host cell. 121,127 Molecular dynamics simulations have shown that TQ can interfere with the attachment of SARS-CoV-2 to host cells by binding to a cell surface, HSPA5, which is recognized by the viral spike protein and upregulated upon viral infection. 128,129 These in silico studies indicate a multi-targeted potential for TQ against COVID-19, and thus pave the way for further investigation of such anti-COVID-19 potential through invitro and in-vivo studies that may better support translation into clinical practice.…”
Section: Molecular Docking Studies Related To Anti-covid-19 Activitymentioning
confidence: 99%
“…Экстракты из растений нигеллы посевной могут быть использованы в качестве антималярийного средства [62]. Особый интерес вызывают последние исследования ряда ученых [63][64], показывающих большую перспективность нигеллы посевной в профилактике и лечении COVID-19, что еще раз подтверждает уникальность этого растения.…”
Section: рис2 структурные формулы изохинолиновых и пиразоловых алкалоидов Fig 2 Structural Formulas Of Isoquinoline and Pyrazole Alkaloidunclassified